Pengaruh Respon Organisasi Dan Power Distance Terhadap Niat Melakukan Whistleblowing - Aning Santi Lestari; Sany Dwita (Jurnal Eksplorasi Akuntansi, 2020)
This study investigates a number of factors influencing employees to report unethical behavior in their organizations. This study aims to empirically examine the effect of organizational response on whistleblowing intentions, the effect of power distance on whistleblowing intentions. This research uses quasi-experimental design. The difference between this research and previous research is in the research data sources. This study collected data with a survey questionnaire given to 64 accounting students from a university in Padang, the capital of West Sumatra. Data were analyzed using ANOVA. The results of this study indicate that strong organizational responses do not have a negative impact on whistleblowing intentions. We also find that low power distances have a positive impact on whistleblowing intentions. The results of this study indicate that power distance affects the intention of revealing facts. These results contribute to the existing literature on accounting ethics, as well as inform public accounting governance policies